Perbandingan Keefektifan Model Pembelajaran Problem Based Learning (PJBL) Dan Inkuiri Terhadap Penguasaan Konsep dan Peningkatan Hasil Belajar Siswa Mengenai Materi Kemagnetan - Mila Inayah; Asih Wulandari; Nenden Permas Hikmatunisa; Dinda Hudaya Nur Fadillah; Silva Gea Delarosa; Rizki Nurul Muslih; Amanda Zahira; Syahira Ramadhini; Alya Latifa (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This study was carried out because of awareness of the importance of innovative and creative learning to overcome obstacles to students' understanding and learning outcomes in magnetic material. With the need for more innovative and creative learning strategies, the author wants to compare the Project Based Learning (PjBL) learning model and the Inquiry learning model on concept mastery and improving student learning outcomes regarding magnetism material. This abstract discusses the comparison of the effectiveness of the Problem Based Learning (PjBL) and Inquiry learning models in mastering concepts and improving student learning outcomes in the context of magnetic material. This research uses the Content Analysis method where the author analyzes several journals which contain two different learning models. The research results show that the two learning models make a positive contribution to students' understanding of concepts and learning outcomes. However, comparative analysis of learning outcomes shows that there is a significant difference between the effectiveness of the Project Based Learning (PjBL) learning model and the Inquiry learning model. The impact of this learning method can help develop more appropriate learning strategies in teaching magnetism material in educational environments. Keywords: Effectiveness, Magnetism, Project Based Learning, Inquiry.